Railways in Developing Countries : A Global Review - World Bank (Washington, DC: World Bank, 2022)
As a green mode of transportation, railways have an important role to play in decarbonizing transport through shifting transport from more polluting modes of transport such as road and air. Railways can enable economic growth, which in turn generates increasing transport demand, while keeping greenhouse gas (GHG) emissions low. However, in many parts of the world, railways have lost traffic and market share to air and road transport modes. As countries seek to reduce their GHG emissions, while still delivering on economic growth, many are rethinking the role of rail. Many developing countries have existing railway networks, which will provide the starting point for efforts to increase rail in the transport mix. This report provides a basic stocktaking of those railways, explaining the industry structure and the current situation. Basic data on network size; volume; passenger fares and freight tariffs; labor productivity; network density; and perceived service quality assets, traffic, pricing and staffing have been compiled into the Developing Country Rail Database, which could be useful for analysis and comparisons across regions. The data have been collected from various public sources—annual railway or regulator reports and/or national statistical annuals. Most data are for 2018. The report covers railways providing services to the general public in 77 countries. Not included are the railways in most higher income countries (North America, Europe, Australasia, and northeast Asia), private mining railways and China, whose railway network has been covered in numerous other reports. The information shared in this report is presented in seven regional summaries, which group together railways sharing a common geographic area and other characteristics: South America; Sub-Saharan Africa; South Asia; Southeast Asia; the Commonwealth of Independent States (CIS) and Mongolia; and the Middle East. These summaries include basic data on institutional arrangements.